The Effect of Publicly Provided Health Insurance on Education Outcomes in Mexico - Alcaraz, Carlo; Chiquiar, Daniel; Orraca, Maria Jose; Salcedo, Alejandrina (Published by Oxford University Press on behalf of the World Bank, 2019)
In this paper we study the causal effect of a large expansion of publicly provided health insurance on school enrollment rates and on children’s academic performance using the case of Mexico. Access to free health insurance could improve education outcomes directly by making household members healthier or indirectly by raising the amount of resources available for education expenses. Using a panel of municipalities from 2007 to 2010, we find that the expansion of the Mexican public health insurance program, Seguro Popular, had a large positive, statistically significant effect on school enrollment rates and on standardized test scores.